AR university logo: markerless mobile augmented reality with waze application integration - Abdullah, Samir Diler (2015)
The university logo represents the entity symbol for the university. Each university has its unique logo in term of design. Since there are variants of design for each logo, it is difficult for people to remember the name or other information of the University related to university logo. Apart from that, the logo itself cannot convey much information to the people. Therefore, current progress in AR technology has come to solve these problems. This project is using Markerless AR technology to track and identified university logo for people. The identification process can deliver information to the user including university name, homepage website and geographical location of university. There are three main elements to be concerned in the development of this project application. The elements are android mobile application concept, interaction with the user and tracking of university logo to identify the university with information deliver to the user by just capturing the photo image. Based on the experiments, 83% strongly agree that adding AR to University Logo helps give University information/direction to University. As a conclusion, AR can solve the problem by convey more information on University Logo.